PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN TOUR PACKAGE PT SMAILING TOUR DI BALI - Artawan, I Putu Pranadita; Ekawati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
This study aims to determine the effect of marketing mix (7P) on packed purchasing decisions on the Smailing Tour. This research method uses multiple linear regression analysis. The population of this study is Smailing Tour consumers in Sanur, Denpasar. The sample from this study was 125 respondents. The data collection method used is questionnaire. The scale used is the Likert scale. The results of this study are product, price, place, promotion, people, process, and physical evidence that have a positive and significant effect on the purchasing decisions packed on the Smailing Tour partially or simultaneously. The R2 of this study is 0.707, which means that 70.7 percent of the purchasing decisions are influenced by the seven variables in this study, the remaining 29.3 percent are influenced by other variables outside the research. this study provides theoretical implications for the development of marketing management science, especially the marketing mix (7P) for purchasing decisions. The managerial implication in this study is that companies need to design creative marketing strategies in order to increase consumer purchasing decisions such as through strategies related to people and prices.